Exploring the pathogenesis of pulmonary vascular disease - Ejikeme, Chidinma; Safdar, Zeenat (Frontiers in Medicine, 2024)
Pulmonary hypertension (PH) is a complex cardiopulmonary disorder impacting the lung vasculature, resulting in increased pulmonary vascular resistance that leads to right ventricular dysfunction. Pulmonary hypertension comprises of 5 groups (PH group 1 to 5) where group 1 pulmonary arterial hypertension (PAH), results from alterations that directly affect the pulmonary arteries. Although PAH has a complex pathophysiology that is not completely understood, it is known to be a multifactorial disease that results from a combination of genetic, epigenetic and environmental factors, leading to a varied range of symptoms in PAH patients. PAH does not have a cure, its incidence and prevalence continue to increase every year, resulting in higher morbidity and mortality rates. In this review, we discuss the different pathologic mechanisms with a focus on epigenetic modifications and their roles in the development and progression of PAH. These modifications include DNA methylation, histone modifications, and microRNA dysregulation.Understanding these epigenetic modifications will improve our understanding of PAH and unveil novel therapeutic targets, thus steering research toward innovative treatment strategies.